Contribution of pectin-degrading bacteria to the quality of cigar fermentation: an analysis based on microbial communities and physicochemical components - Su, Youbo; Cui, Yonghe; Fu, Kejian; Bu, Lingduo; Sun, Yucui; Zhou, Qi; Yin, Yuming; Sun, Yulong; Yang, Huating; Wu, Lang; Song, Xueru (Frontiers in Microbiology, 2024)
ObjectiveThis study aims to investigate the effects of pectin-degrading bacteria on the microbial community and physicochemical properties during the fermentation process of cigar tobacco, evaluating its potential in reducing green bitterness and enhancing aroma.MethodsBy isolating and screening pectin-degrading bacteria, high-throughput sequencing and physicochemical analysis were employed to compare the microbial flora and physicochemical component differences in different treatment groups of cigar tobacco. Furthermore, correlation analysis was performed to examine the relationships between these variables.ResultsThe results showed that the strains YX-2 and DM-3, isolated from the cigar tobacco variety “Yunxue No. 1,” exhibited strong pectin-degrading abilities. Phylogenetic analysis revealed that strain YX-2 is highly homologous to Bacillus flexus, while strain DM-3 is highly homologous to Bacillus siamensis. After fermentation, the addition of strains YX-2 and DM-3 significantly reduced the pectin content in the tobacco leaves, increased the total sugar and reducing sugar content, reduced green bitterness, and markedly enhanced the total aroma components. Notably, DM-3 exhibited outstanding performance in the production of Maillard reaction products. Microbial community analysis showed that the addition of pectin-degrading bacteria significantly increased the diversity of both bacteria and fungi, especially in the TDM3 group, where the relative abundance of Pseudomonas was notably elevated. Correlation analysis revealed that Pseudomonas had a significant positive correlation with both reducing sugar and total sugar, and a significant negative correlation with pectin, indicating its important role in sugar metabolism and pectin degradation. Additionally, fungal genera such as Cercospora were significantly negatively correlated with total sugar and total nitrogen, while Eurotium was closely associated with pectin degradation and reducing sugar accumulation.ConclusionThis study found that the addition of Pectin-degrading bacteria YX-2 and DM-3 significantly optimized the microbial community structure during the cigar tobacco fermentation process and improved the physicochemical properties of the tobacco leaves, with notable effects in reducing green bitterness and enhancing aroma.